Analytical study of entrepreneurship state in Russia - A. A. Buimov (Вестник университета)
The purpose of the study is to provide a comprehensive analytical overview of small and medium-sized enterprises (hereinafter – SMEs) state in Russia. The main part is divided into four subsections and shows SMEs development trends, analysis of small business by industries and a comparative review of sociological surveys among entrepreneurs. The paper concludes by identifying the institutional factors that determine the level of entrepreneurial activity by Russian regions and compiling regression models. The share of SMEs in the country’s economy remains low and the number of entities tends to decrease, while the population’s desire to engage in entrepreneurship is also decreasing. An analysis of activity by sector shows that most SMEs operate in the service sector and larger enterprises prefer to operate in more basic sectors of the economy, while most markets are dominated by large businesses. A sociological surveys comparative analysis allowed us to draw an average portrait of entrepreneurs; the data from the surveys generally converge with official statistics. An extremely high variability in the level of entrepreneurial activity across Russian regions has been shown. For this reason, more than two dozen regional social and economic indicators have been selected and correlation analysis carried out. Regression models of entrepreneurial activity have been compiled on the basis of these indicators.